Sulfonyl post-modified conjugated microporous polymer cesium adsorbent and preparation method thereof
By introducing sulfonic acid groups into the conjugated microporous polymer and carrying out post-modification reaction, a conjugated microporous polymer cesium adsorbent with high adsorption capacity and good stability was prepared, and Cs+ in the prior art was solved The problems of low ion adsorption capacity and high cost achieve efficient adsorption and removal of Cs+ ions in aqueous solution.
Patent Information
- Application Number
- CN202411591826.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art has problems such as high cost, poor stability and low adsorption capacity in the process of removing Cs+ ions in aqueous solution, which is difficult to meet the effective adsorption needs of radioactive elements in mined sewage.
The fully conjugated polymer network structure with porous structure was prepared by cross-coupling reaction, and the post-sulfonic acid group modification reaction was carried out under nitrogen protection. The reaction was terminated and the pH was replaced to neutral. The post-sulfonic acid group modification was prepared by vacuum drying. Microporous polymer cesium adsorbent.
The adsorbent has a graded porous structure, open permanent micropores, continuous π-conjugated framework, rich sulfonic acid binding sites, excellent adsorption capacity, and good acid-base tolerance and cycle stability. The preparation process is simple, The conditions are mild.
Smart Images

Figure CN119455909A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of radioactive element adsorbents, and in particular to a sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent and a preparation method thereof. Background Art
[0002] With the increase in the use of nuclear energy and radioactive materials, the problem of radioactive element pollution in the environment has become increasingly prominent, especially in the process of mining and resource extraction. 137 Cs, 235 U. 90 Sr. 3 H and 106 Radioactive elements such as Ru. Among them, 235 The radioactive elements that often appear in nuclear waste produced by U are 137 Cs. It is a high-energy thermal fission nuclide that decays for up to 30 years. Its decay gamma rays can destroy biological cells and tissues. + The ion has high mobility and good solubility, so organisms can easily access Cs in aqueous solution. + Ion. Radioactive Cs + The ions enter the human body through the food chain and accumulate in the bones and muscle tissues through blood circulation. At a certain dose, they can cause radiation damage to the human body, cause the growth of soft tissue tumors, and lead to cancer. Therefore, there is an urgent need for a method that can effectively remove Cs from aqueous solutions. + Ionic method.
[0003] Currently, the separation of Cs from nuclear wastewater + Common methods for removing ions include precipitation, extraction and ion exchange. (1) Precipitation can effectively remove high concentrations of Cs + ions, but using a system with a low concentration of the target substance will greatly increase the cost. For complex systems, the adsorption is not high and the selectivity is not strong; (2) The selectivity of solvent extraction is high and can effectively remove Cs in low concentration systems + ions, but the extractant is easily lost and needs to be used in a strong acid or alkaline environment. A large amount of organic solvent needs to be added during the production process to ensure the fluidity of the extraction phase. The high cost of post-processing limits the breakthrough of this technology; (3) The ion exchange method adsorbs ions through the exchange reaction between the ion exchanger and the specific ions in the solution. The main factors affecting the ion exchange capacity include the specific surface area, structure, stirring time and temperature of the ion exchanger. The ion exchange method is an extremely advanced technology that is extremely effective in enriching and recovering trace radioactive nuclides. It has the advantages of large adsorption capacity, strong reversibility, reusability, good selectivity, low cost and low pollution. However, traditional organic adsorbents also have the disadvantages of high cost, poor stability and poor selectivity for Cs +The poor adsorption capacity of ions limits its practical application. + New adsorbents with strong ion binding ability, large adsorption capacity, low cost and good physicochemical stability have important application prospects.
[0004] Porous organic materials such as metal organic frameworks (MOFs) and hypercrosslinked polymers (HCPs) have been widely used in Cs + HCPs have a high specific surface area, but their synthesis requires the use of strong Lewis acids such as FeCl 3 or other hydrochlorides. Under such harsh conditions, it may be difficult to introduce certain functional groups into the polymer, which greatly limits the application of HCPs to Cs + Enhanced ion adsorption capacity. MOFs have poor stability, complex synthesis process, and difficulty in industrial production, which limits their practical application. Conjugated microporous polymers (CMPs) are a type of organic porous polymer. Compared with traditional conjugated polymers or porous materials, they have the characteristics of a π-conjugated skeleton and a large number of micropores, making them an important adsorption material. The skeleton structure of CMPs has an electron-rich conjugated system and contains abundant rigid binding sites. Doping electron-rich groups in the carbon skeleton can improve the adsorption performance. Since the lone pair electrons of the electron-rich group can enhance the interaction between the adsorbent and the metal ions, the introduction of electron-rich groups into the CMPs skeleton is expected to enhance the adsorption with Cs + Interaction of ions.
[0005] Electron-rich sulfonic acid groups are a common type of functional group in cation exchange resins. + Sulfonic acid ion exchangers have been widely used to adsorb UO 2 2+ , Sr 2+ 、Ni 2+ , Pb 2+ plasma, and to Cs + However, the current study shows that the adsorption of low concentration Cs + The removal effect of ions is not ideal, and the adsorption speed is slow. Therefore, electron-rich sulfonic acid groups are introduced into CMPs as adsorbents to selectively adsorb Cs in aqueous solutions. + Ions are a promising class of Cs + Ion adsorbing materials. Summary of the invention
[0006] Purpose of the invention: In order to meet the demand for adsorption of radioactive elements in mine wastewater, the present invention adopts a cross-coupling reaction to prepare a porous fully conjugated polymer network structure, mixes it with a sulfonic acid group and a reaction solvent under nitrogen protection to carry out a sulfonic acid post-modification reaction, terminates the reaction by a quencher and replaces the pH to neutral, and adopts vacuum drying to prepare a sulfonic acid post-modified conjugated microporous polymer cesium adsorbent. The adsorbent not only has a series of advantages such as hierarchical porous structure, open permanent micropores, continuous π-conjugated skeleton, rich sulfonic acid binding sites, and excellent adsorption capacity, but also has good acid-base tolerance and cyclic stability, and the preparation process is simple and the conditions are mild. It is a high-performance radioactive element adsorbent with broad prospects.
[0007] The present invention provides a sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent and a preparation method thereof, which comprises the following steps:
[0008] Step S1, preparing a porous fully conjugated polymer network: placing a bromine functional building block, an alkyne structural building block, a catalyst and a reaction solvent in a round-bottom flask under an argon environment, and performing a high-temperature continuous reaction by a cross-coupling method, and preparing a porous fully conjugated polymer network by Soxhlet extraction;
[0009] Step S2, preparing a sulfonic acid group post-modified polymer network: injecting the porous fully conjugated polymer network into a reaction solvent under nitrogen protection, stirring at low temperature (generally at room temperature of 25° C.), and then dropwise adding sulfonic acid groups in an ice bath for sufficient reaction to prepare a sulfonic acid group post-modified polymer network;
[0010] Step S3, preparing a sulfonic acid post-modified conjugated microporous polymer cesium adsorbent: after the porous fully conjugated polymer network and the sulfonic acid group are fully sulfonated in the reaction solvent, the reaction is terminated with a quencher, the pH of the system is replaced with a solvent to be neutral, and vacuum drying is used to prepare a conjugated microporous polymer cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites.
[0011] In step S1, the alkyne structural building block is 1,3,5-triethynylbenzene, the bromine functional building block is at least one of tetra-4-bromostyrene, 1,2-di-4-bromophenyl-1,2-stilbene, 1,2-bis-4-bromophenyl-1,2-stilbene, and 3,3',6,6'-tetrabromo-9,9'-difluorene subunit, and the molar ratio of the bromine functional building block to the alkyne structural building block is 1:1 to 2:1.
[0012] In step S1, the catalyst is tetrakistriphenylphosphine palladium and cuprous iodide, and the molar ratio of the tetrakistriphenylphosphine palladium to cuprous iodide is 1:1 to 2:1.
[0013] In step S1, the reaction solvent is at least one of toluene, N,N-dimethylformamide, 1-dichloroethane, 2-dichloroethane, and tetrahydrofuran, and the reaction solvent is mixed with triethylamine, and the volume ratio of the reaction solvent to triethylamine is 1:1 to 2:1.
[0014] In step S1, the temperature of the high temperature continuous reaction is 80-100° C., and the reaction time is 36-72 hours.
[0015] In step S1, the solvents used in the solvent replacement are dichloromethane, chloroform, acetone, deionized water and methanol in sequence, and the solvent used in the Soxhlet extraction is at least one of methanol, chloroform and dichloromethane.
[0016] In step S2, the sulfonic acid group is at least one of chlorosulfonic acid, concentrated sulfuric acid, sulfonyl chloride, and benzenesulfonic acid, and the sulfonation time is 4 to 48 hours.
[0017] In step S2, the reaction solvent is at least one of dichloromethane, chloroform, N,N-dimethylformamide, and glacial acetic acid.
[0018] In step S3, the quencher is at least one of deionized water, ammonia water, sodium hydroxide and ethanol.
[0019] The present invention also provides a sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent, which is prepared by the method and can be used for the adsorption and removal of radioactive elements in sewage during mine mining.
[0020] Beneficial effects: The present invention provides a sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent and a preparation method thereof, wherein a fully conjugated polymer network structure with a porous structure is prepared by a cross-coupling reaction, and a sulfonic acid group and a reaction solvent are mixed under nitrogen protection to carry out a sulfonic acid group post-modification reaction, and a quencher is used to terminate the reaction and replace the pH value to neutral, and vacuum drying is used to prepare a sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent, wherein the specific surface area of the adsorbent is 74-225 m 2 / g, average pore size is 1.10-2.06nm, sulfonic acid group density is 6.32-9.18mg / m 2 , cesium ion adsorption ≥90%, not only has a series of advantages such as hierarchical porous structure, open permanent micropores, continuous π-conjugated skeleton, rich sulfonic acid binding sites, excellent adsorption capacity, but also has good acid-base tolerance and cyclic stability, the preparation process is simple and the conditions are mild. It is a high-performance radioactive element adsorbent with broad prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0022] Figure 1 is a scanning electron microscope image of the sulfonic acid-based adsorbent in Example 1.
[0023] Figure 2 is a transmission electron microscope image of the sulfonic acid-based adsorbent in Example 1.
[0024] Figure 3 is the Fourier transform infrared spectrum of the sulfonic acid adsorbent in Example 1.
[0025] Figure 4 is the powder X-ray diffraction spectrum of the sulfonic acid adsorbent in Example 1.
[0026] Figure 5 3 is a nitrogen adsorption-desorption isotherm diagram of the sulfonic acid-based adsorbent in Example 1.
[0027] Figure 6 is a scanning electron microscope image of the sulfonic acid-based adsorbent in Example 2.
[0028] Figure 7 is a transmission electron microscope image of the sulfonic acid-based adsorbent in Example 2.
[0029] Figure 8 This is the Fourier transform infrared spectrum of the sulfonic acid adsorbent in Example 2.
[0030] Fig. 9 This is the powder X-ray diffraction spectrum of the sulfonic acid adsorbent in Example 2.
[0031] Fig.10 3 is a nitrogen adsorption-desorption isotherm diagram of the sulfonic acid-based adsorbent in Example 2.
[0032] Fig.11 is a scanning electron microscope image of the sulfonic acid-based adsorbent in Example 3.
[0033] Fig.12 is a transmission electron microscope image of the sulfonic acid-based adsorbent in Example 3.
[0034] Fig.13 This is the Fourier transform infrared spectrum of the sulfonic acid adsorbent in Example 3.
[0035] Fig.14 This is the powder X-ray diffraction spectrum of the sulfonic acid adsorbent in Example 3.
[0036] Fig.15 is a pore size distribution curve diagram of the sulfonic acid-based adsorbent in Example 3.
[0037] Fig.16 is a scanning electron microscope image of the sulfonic acid-based adsorbent in Example 4.
[0038] Fig.17 is a transmission electron microscope image of the sulfonic acid-based adsorbent in Example 4.
[0039] Fig.18 This is the Fourier transform infrared spectrum of the sulfonic acid adsorbent in Example 4.
[0040] Fig.19 This is the powder X-ray diffraction spectrum of the sulfonic acid adsorbent in Example 4.
[0041] Fig. 20 This is a pore size distribution curve of the sulfonic acid-based adsorbent in Example 4.
[0042] Fig.21 It is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0043] Example 1
[0044] like Fig.21 As shown, this embodiment provides a method for preparing a sulfonic acid group-post-modified conjugated microporous polymer cesium adsorbent, comprising the following steps:
[0045] S11. Preparation of a porous fully conjugated polymer network: 1,3,5-triethynylbenzene, tetra-4-bromostyrene (molar ratio of 1:2), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 1:1), toluene and triethylamine (volume ratio of 4:3) were reacted continuously at 85°C for 48 hours under argon protection, and a porous fully conjugated polymer network was prepared by Soxhlet extraction;
[0046] S12. Preparation of sulfonic acid post-modified polymer network: The porous fully conjugated polymer network prepared in S11 was injected with 50 mL of dichloroethane under nitrogen protection and stirred at 25°C for 1 hour. Under ice bath conditions, chlorosulfonic acid (150 μmol) was added dropwise and reacted for 48 hours to prepare a sulfonic acid post-modified polymer network;
[0047] S13. Preparation of sulfonic acid post-modified conjugated microporous polymer cesium adsorbent: The sulfonic acid post-modified polymer network prepared in S12 was terminated by using deionized water as a quencher, and the pH of the system was neutralized by solvent replacement and vacuum drying to prepare a conjugated microporous polymer cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites, with a specific surface area of 225 m 2 / g, and the average pore size is 1.10nm.
[0048] Figure 1 This is a scanning electron microscope image of the sulfonic acid-based adsorbent obtained in Example 1, which shows that the material is a dense three-dimensional network structure formed by random weaving of nanotubes.
[0049] Figure 2This is a transmission electron microscope image of the sulfonic acid-based adsorbent obtained in Example 1, which shows that the nanotubes are hollow structures with an inner diameter of 40 to 120 nm and an outer diameter of 150 to 200 nm.
[0050] Figure 3 This is the Fourier transform infrared spectrum of the sulfonic acid adsorbent obtained in Example 1, which shows that the material structure has stretching vibrations representing characteristic peaks such as -C≡C-, -S=O, and -CS-.
[0051] Figure 4 This is the powder X-ray diffraction pattern of the sulfonic acid-based adsorbent obtained in Example 1, indicating that the material has an amorphous structure with short-range order and long-range disorder.
[0052] Figure 5 The nitrogen adsorption-desorption isotherm curve of the sulfonic acid-based adsorbent obtained in Example 1 shows that the material has a wide specific surface area.
[0053] Example 2
[0054] This embodiment provides a method for preparing a sulfonic acid group-post-modified conjugated microporous polymer cesium adsorbent, comprising the following steps:
[0055] S21. Preparation of a porous fully conjugated polymer network: 1,3,5-triethynylbenzene, 1,2-di-4-bromophenyl-1,2-diphenylethylene (molar ratio of 2:3), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 2:3), N,N-dimethylformamide and triethylamine (volume ratio of 4:3) were reacted continuously at 80°C for 72 hours under argon protection to prepare a porous fully conjugated polymer network by Soxhlet extraction;
[0056] S22. Preparation of sulfonic acid post-modified polymer network: The porous fully conjugated polymer network prepared in S21 was injected with 50 mL of trichloroethane under nitrogen protection and stirred at 25°C for 1 hour. In an ice bath, concentrated sulfuric acid (150 μmol) was added dropwise and reacted for 24 hours to prepare a sulfonic acid post-modified polymer network;
[0057] S23. Preparation of sulfonic acid post-modified conjugated microporous polymer cesium adsorbent: The sulfonic acid post-modified polymer network prepared in S22 was terminated by using ammonia as a quencher, and the pH of the system was neutralized by solvent replacement and vacuum drying to prepare a conjugated microporous polymer cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites, with a specific surface area of 209 m 2 / g, and the average pore size is 1.22nm.
[0058] Figure 6 This is a scanning electron microscope image of the sulfonic acid-based adsorbent obtained in Example 2, which shows that the material is a dense three-dimensional network structure formed by random weaving of nanotubes.
[0059] Figure 7This is a transmission electron microscope image of the sulfonic acid-based adsorbent obtained in Example 2, which shows that the nanotubes are hollow structures with an inner diameter of 40 to 120 nm and an outer diameter of 150 to 200 nm.
[0060] Figure 8 This is the Fourier transform infrared spectrum of the sulfonic acid adsorbent obtained in Example 2, which shows that the material structure has stretching vibrations representing characteristic peaks such as -C≡C-, -S=O, and -CS-.
[0061] Fig. 9 This is the powder X-ray diffraction pattern of the sulfonic acid-based adsorbent obtained in Example 2, indicating that the material has an amorphous structure with short-range order and long-range disorder.
[0062] Fig.10 This is the nitrogen adsorption-desorption isotherm of the sulfonic acid-based adsorbent obtained in Example 2, indicating that the material has a wide specific surface area.
[0063] Example 3
[0064] This embodiment provides a method for preparing a sulfonic acid group-post-modified conjugated microporous polymer cesium adsorbent, comprising the following steps:
[0065] S31. Preparation of a porous fully conjugated polymer network: 1,3,5-triethynylbenzene, 1,2-bis-4-bromophenyl-1,2-stilbene (molar ratio of 3:2), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 3:2), 1,2-dichloroethane and triethylamine (volume ratio of 4:3) were reacted continuously at 90°C for 60 hours under argon protection to prepare a porous fully conjugated polymer network by Soxhlet extraction;
[0066] S32. Preparation of sulfonic acid post-modified polymer network: The porous fully conjugated polymer network prepared in S31 was injected with 50 mL of N,N-dimethylformamide under nitrogen protection and stirred at 25°C for 1 hour. In an ice bath, sulfonyl chloride (150 μmol) was added dropwise and reacted for 12 hours to prepare a sulfonic acid post-modified polymer network;
[0067] S33. Preparation of sulfonic acid post-modified conjugated microporous polymer cesium adsorbent: The sulfonic acid post-modified polymer network prepared in S32 was terminated by using sodium hydroxide as a quencher, and the pH of the system was neutralized by solvent replacement and vacuum drying to prepare a conjugated microporous polymer cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites, with a specific surface area of 193 m 2 / g, and the average pore size is 1.56nm.
[0068] Fig.11 This is a scanning electron microscope image of the sulfonic acid-based adsorbent obtained in Example 3, which shows that the material is a dense three-dimensional network structure formed by random weaving of nanotubes.
[0069] Fig.12 This is a transmission electron microscope image of the sulfonic acid-based adsorbent obtained in Example 3, indicating that the nanotubes are hollow structures with an inner diameter of 40 to 120 nm and an outer diameter of 150 to 200 nm.
[0070] Fig.13 This is the Fourier transform infrared spectrum of the sulfonic acid adsorbent obtained in Example 3, indicating that the material structure has stretching vibrations representing characteristic peaks such as -C≡C-, -S=O, and -CS-.
[0071] Fig.14 The powder X-ray diffraction pattern of the sulfonic acid-based adsorbent obtained in Example 3 shows that the material has an amorphous structure with short-range order and long-range disorder.
[0072] Fig.15 This is the pore size distribution curve of the sulfonic acid-based adsorbent obtained in Example 3, indicating that the material has a narrow pore size.
[0073] Example 4
[0074] This embodiment provides a method for preparing a sulfonic acid group-post-modified conjugated microporous polymer cesium adsorbent, comprising the following steps:
[0075] S41. Preparation of a porous fully conjugated polymer network: 1,3,5-triethynylbenzene, 3,3',6,6'-tetrabromo-9,9'-difluorene (molar ratio of 2:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 2:1), tetrahydrofuran and triethylamine (volume ratio of 4:3) were reacted continuously at 100°C for 36 hours under argon protection to prepare a porous fully conjugated polymer network by Soxhlet extraction;
[0076] S42. Preparation of sulfonic acid post-modified polymer network: The porous fully conjugated polymer network prepared in S41 was injected with 50 mL of glacial acetic acid under nitrogen protection and stirred at 25°C for 1 hour. In an ice bath, benzenesulfonic acid (150 μmol) was added dropwise and reacted for 4 hours to prepare a sulfonic acid post-modified polymer network;
[0077] S43. Preparation of sulfonic acid post-modified conjugated microporous polymer cesium adsorbent: The sulfonic acid post-modified polymer network prepared in S42 was terminated by using ethanol as a quencher, and the pH of the system was neutralized by solvent replacement and vacuum drying to prepare a conjugated microporous polymer cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites, with a specific surface area of 191 m 2 / g, and the average pore size is 1.54nm.
[0078] Fig.16 This is a scanning electron microscope image of the sulfonic acid-based adsorbent obtained in Example 4, which shows that the material is a dense three-dimensional network structure formed by random weaving of nanotubes.
[0079] Fig.17 This is a transmission electron microscope image of the sulfonic acid-based adsorbent obtained in Example 4, which shows that the nanotubes are hollow structures with an inner diameter of 40 to 120 nm and an outer diameter of 150 to 200 nm.
[0080] Fig.18 This is the Fourier transform infrared spectrum of the sulfonic acid adsorbent obtained in Example 4, which shows that the material structure has stretching vibrations representing characteristic peaks such as -C≡C-, -S=O, and -CS-.
[0081] Fig.19 This is the powder X-ray diffraction pattern of the sulfonic acid-based adsorbent obtained in Example 4, indicating that the material has an amorphous structure with short-range order and long-range disorder.
[0082] Fig. 20 This is the pore size distribution curve of the sulfonic acid-based adsorbent obtained in Example 4, indicating that the material has a narrow pore size.
[0083] Comparative Example 1 (adding two bromine functional building blocks)
[0084] The sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent was prepared by basically adopting the method of Example 1. The difference is that in this example, two bromine functional building blocks were added to react with the alkyne structural building blocks to prepare a porous fully conjugated polymer network. Specifically, 1,3,5-triethynylbenzene, tetra-4-bromostyrene, 1,3,5-tribromobenzene (molar ratio of 1:1:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 1:1), toluene and triethylamine (volume ratio of 4:3) were reacted continuously at 85°C for 48 hours under argon protection, and a porous fully conjugated polymer network was prepared by Soxhlet extraction; 50 mL of dichloroethane was injected into the porous fully conjugated polymer network under nitrogen protection and stirred at 25°C for 1 hour, and chlorosulfonic acid (150 μmol) was added dropwise in an ice bath to react for 48 hours to prepare a sulfonic acid group-modified polymer network; deionized water was used as a quencher to terminate the reaction, and the pH of the solvent replacement system was neutral, and then vacuum dried to prepare a conjugated microporous polymer cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites, with a specific surface area of 147 m 2 / g, and the average pore size is 1.73nm.
[0085] Comparative Example 2 (Preparation of a porous fully conjugated polymer network using a hydrothermal synthesis method)
[0086] The method of Example 2 was basically used to prepare a sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent. The difference is that this example uses a hydrothermal synthesis method to prepare a porous fully conjugated polymer network for sulfonation post-modification. Specifically, 1,3,5-triethynylbenzene, 1,2-di-4-bromophenyl-1,2-stilbene (molar ratio of 2:3), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 2:3), N,N-dimethylformamide and triethylamine (volume ratio of 4:3) were placed in a reactor at 80°C for continuous reaction for 72 hours, and a porous fully conjugated polymer network was prepared by Soxhlet extraction; the porous fully conjugated polymer network was injected with 50mL of trichloroethane under nitrogen protection and stirred at 25°C for 1 hour. In an ice bath, concentrated sulfuric acid (150 μmol) was added dropwise for 24 hours to prepare a sulfonic acid post-modified polymer network. Ammonia was used as a quencher to terminate the reaction, and the pH of the system was neutralized by solvent replacement. After vacuum drying, a conjugated microporous polymer cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites was prepared. The specific surface area was 139 m 2 / g, and the average pore size is 1.77nm.
[0087] Comparative Example 3 (without addition of sulfonic acid group)
[0088] The conjugated microporous polymer cesium adsorbent was prepared by basically adopting the method of Example 3. The difference is that no sulfonic acid group was added during the synthesis process in this example. Specifically, 1,3,5-triethynylbenzene, 1,2-bis-4-bromophenyl-1,2-stilbene (molar ratio of 3:2), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 3:2), 1,2-dichloroethane and triethylamine (volume ratio of 4:3) were reacted continuously at 90°C for 60 hours under argon protection, and a porous fully conjugated polymer cesium adsorbent with a specific surface area of 74 m was prepared by Soxhlet extraction. 2 / g, and the average pore size is 2.06nm.
[0089] Structural characterization and performance testing:
[0090] Scanning electron microscope observation: The microstructure of the conjugated microporous polymer-carbon nanotube composite filtration membrane was observed by field emission scanning electron microscope (model JSM-7900F, Japan Electronics). Figure 1 , Figure 6 , Fig.11 , Fig.16 ).
[0091] Transmission electron microscopy observation: The microstructure of the conjugated microporous polymer-carbon nanotube composite filtration membrane was observed by field emission transmission electron microscopy (model TECNI G2 TF20, FEI Company, the Netherlands). Figure 2 , Figure 7 , Fig.12 , Fig.17 ).
[0092] Functional group structure test: An infrared spectrometer (model VERTEX 70, Bruker, USA) was used to record the functional groups (such as Figure 3 , Figure 8 , Fig.13 , Fig.18 As shown, in the figure, Transmittance represents transmittance and Wavenumber represents wave number).
[0093] Crystal structure test: An X-ray spectrometer (model D / Max-2400, Rigaku Corporation, Japan) was used to record the crystal structure of the conjugated microporous polymer-carbon nanotube composite filter membrane (e.g. Figure 4 , Fig. 9 , Fig.14 , Fig.19 As shown, Intensity represents intensity and 2Theta represents 2θ diffraction angle).
[0094] Specific surface area test: A gas adsorption instrument (ASAP 2060, Micromeritics, USA) was used to measure the nitrogen adsorption isotherm at 77K (e.g. Figure 5 , Fig.10 , Fig.15 , Fig. 20 As shown in the figure, Quantity Adsorbed represents the adsorption amount, Relative pressure represents the relative pressure, Pore Volume represents the pore volume, and Pore width represents the pore size).
[0095] Cesium ion adsorption performance test: The concentration of metal cations in aqueous solution was measured using an Elan DRC-e inductively coupled plasma mass spectrometer (PerkinElmer, USA) and a Spectro Arcos II MV inductively coupled plasma optical emission spectrometer (Spektro, Germany).
[0096] Experimental results: Figure 1 , Figure 6 , Fig.11 and Fig.16 As shown, bromine functional building blocks, alkyne structural building blocks, catalysts and reaction solvents are cross-coupled and post-modified to synthesize a cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites. In Example 1, the porous fully conjugated polymer network forms a tubular morphology through bottom-up self-assembly, and forms a three-dimensional network structure through random winding, weaving and arrangement. The post-sulfonation modification does not change the microscopic morphology.
[0097] like Figure 2 , Figure 7 , Fig.12 and Fig.17As shown, the tubular structure is a hollow nanotube with an inner diameter of 40 to 120 nm and an outer diameter of 150 to 200 nm. The tube wall thickness is smooth and uniform, the ends are open and interconnected, and the three-dimensional network structure increases the flow rate per unit volume of the adsorbent, allowing the fluid to quickly enter and exit the material.
[0098] like Figure 3 , Figure 8 , Fig.13 and Fig.18 As shown, at 3270cm -1 The -C≡CH bond formed by triacetin monomer disappears at 2207-2198cm -1 The terminal alkyne and halide establish a stable -C≡C- covalent bond; after sulfonation, the peaks are 1046-1043 and 607-606 cm -1 The stretching vibration peaks of -S=O and -CS- were formed in the range, indicating the successful formation of sulfonic acid reaction.
[0099] like Figure 4 , Fig. 9 , Fig.14 and Fig.19 As shown, the diffraction pattern shows a broad and flat characteristic signal peak at 23°, indicating that the material has an amorphous structure with short-range order and long-range disorder.
[0100] like Figure 5 , Fig.10 , Fig.15 and Fig. 20 As shown in the figure, the adsorption and desorption isotherms show a similar trend, namely, a medium-pressure section where the nitrogen adsorption amount gradually increases and a high-pressure section where nitrogen is rapidly adsorbed. Combined with the pore size distribution curve, it shows that the sulfonated adsorbent has a large specific surface area and a hierarchical porous structure.
[0101] Table 1 compares the specific surface area, pore size, sulfonation density and Cs+ adsorption test results of the sulfonated adsorbents obtained in the examples and comparative examples. Examples 1-4 and comparative examples 1 and 2 have a higher specific surface area (139 m 2 / g-225m 2 / g) and a smaller pore size (1.10nm-1.77nm). This is because the sulfonic acid groups are additionally grafted into the porous fully conjugated skeleton during the post-sulfonation modification process, which realizes the redistribution of the skeleton voids and the effective segmentation of the pore space during the reaction process, thereby generating a larger specific surface area and a smaller pore size. The specific surface area of comparative example 3 is only 74m 2 / g, and the average pore size is 2.06nm, which is due to the uncontrollable and incomplete reaction during the synthesis of the polymer network.
[0102] Table 1
[0103]
[0104]
[0105] The cesium ion adsorption capacity of the sulfonic acid group-modified conjugated microporous polymer adsorbent is closely related to the specific surface area, pore size and sulfonation density. The examples 1-4 and comparative examples 1-2 with broad specific surface area, narrow pore size and abundant sulfonic acid groups have a strong affinity for Cs + The adsorption amount was higher than 90%. Among them, Example 1 with the highest specific surface area, the smallest pore size and the most sulfonic acid groups was + Showing the best affinity and sensitivity, Cs + The adsorption capacity is 99%, which is much higher than that of the comparative example 3 (Cs + The adsorption amount is 3%).
[0106] This shows that the technical solution proposed in the present invention makes the sulfonic acid group post-modified conjugated microporous polymer adsorbent have a series of advantages such as hierarchical porous structure, open permanent micropores, continuous π-conjugated skeleton, abundant sulfonic acid binding sites, and excellent adsorption capacity. These are likely due to: (1) The introduction of sulfonic acid groups provides Cs + ions adsorption sites, the conjugated microporous polymer has a stable rigid structure and can be recycled multiple times as an insoluble powder; (2) the open and permanent microporous structure can enhance the dispersion of sulfonation sites and increase the sulfonation degree of the adsorbent, making Cs + The ions can reach the adsorption site, thereby improving the adsorption capacity and selectivity of the adsorbent; (3) Through the mutual grafting of monomers, the cross-linking agent forms a stable covalent bridge between the monomers, which promotes the extensive distribution of conjugated rings and the enrichment of heteroatoms in the skeleton, giving the adsorbent stronger structural stability and diversity.
[0107] The present invention provides a sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent and a preparation method. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent, characterized in that: The following steps are involved: Step S1, preparing a porous fully conjugated polymer network: placing a bromine functional building block, an alkyne structural building block, a catalyst and a reaction solvent in a round-bottom flask under an argon environment, and performing a high-temperature continuous reaction by a cross-coupling method, and preparing a porous fully conjugated polymer network by Soxhlet extraction; Step S2, preparing a sulfonic acid group post-modified polymer network: injecting the porous fully conjugated polymer network into a reaction solvent under nitrogen protection, stirring at low temperature, and then adding sulfonic acid groups dropwise in an ice bath for full reaction to prepare a sulfonic acid group post-modified polymer network; Step S3, preparing a sulfonic acid post-modified conjugated microporous polymer cesium adsorbent: after the porous fully conjugated polymer network and the sulfonic acid group are fully sulfonated in the reaction solvent, the reaction is terminated with a quencher, the pH of the system is replaced with a solvent to be neutral, and vacuum drying is used to prepare a conjugated microporous polymer cesium adsorbent with a continuous π-conjugated skeleton and abundant sulfonic acid binding sites.
2. The method according to claim 1, characterized in that: In step S1, the alkyne structural building block is 1,3,5-triethynylbenzene, the bromine functional building block is at least one of tetra-4-bromostyrene, 1,2-di-4-bromophenyl-1,2-stilbene, 1,2-bis-4-bromophenyl-1,2-stilbene, and 3,3',6,6'-tetrabromo-9,9'-difluorene subunit, and the molar ratio of the bromine functional building block to the alkyne structural building block is 1:1 to 2:
1.
3. The method according to claim 2, characterized in that In step S1, the catalyst is tetrakistriphenylphosphine palladium and cuprous iodide, and the molar ratio of the tetrakistriphenylphosphine palladium to cuprous iodide is 1:1 to 2:
1.
4. The method according to claim 3, characterized in that In step S1, the reaction solvent is at least one of toluene, N,N-dimethylformamide, 1-dichloroethane, 2-dichloroethane, and tetrahydrofuran, and the reaction solvent is mixed with triethylamine, and the volume ratio of the reaction solvent to triethylamine is 1:1 to 2:
1.
5. The method according to claim 4, characterized in that In step S1, the temperature of the high temperature continuous reaction is 80-100° C., and the reaction time is 36-72 hours.
6. The method according to claim 8, characterized in that In step S1, the solvents used in the solvent replacement are dichloromethane, chloroform, acetone, deionized water and methanol in sequence, and the solvent used in the Soxhlet extraction is at least one of methanol, chloroform and dichloromethane.
7. The method according to claim 5, characterized in that In step S2, the sulfonic acid group is at least one of chlorosulfonic acid, concentrated sulfuric acid, sulfonyl chloride, and benzenesulfonic acid, and the sulfonation time is 4 to 48 hours.
8. The method according to claim 7, characterized in that In step S2, the reaction solvent is at least one of dichloromethane, chloroform, N,N-dimethylformamide, and glacial acetic acid.
9. The method according to claim 8, characterized in that In step S3, the quencher is at least one of deionized water, ammonia water, sodium hydroxide and ethanol.
10. A sulfonic acid group post-modified conjugated microporous polymer cesium adsorbent, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.